Impact of Economic Integration and Information and Communication Technology on Economic Growth in ASEAN and EU Regions - Muhammad Bilal, Ahsin (UNIVERSITI MALAYSIA SARAWAK, 2022)
Economic integration and ICT have emerged as significant contributors to economic growth. Although economic integration and ICT have been increasing over the last few years, economic growth has curbed behavior in the EU and ASEAN regions. The curbed economic growth signifies exploring the impact of economic integration and ICT in both regions. So, in light of endogenous growth theory and new trade theory, this study investigates the impact of economic integration and ICT on economic growth for EU and ASEAN regions. Additionally, the existence of the digital divide in the EU and ASEAN regions has been a prime concern for governing bodies of the EU and ASEAN. To address the digital divide issue, this study explores the role of ICT for economic integration and growth nexus concerning ICT usage and readiness. Further, this study identifies precise threshold levels considering ICT readiness and usage for both regions. The study used dynamic panel Generalized Method of Moments (GMM) and dynamic panel threshold regression techniques to avoid endogeneity. The results confirmed the dynamic impact of economic growth in both EU and ASEAN regions. The results revealed that the impact of economic integration is positive and significant on economic growth for both ASEAN and EU regions. However, the impact is more substantial in the EU region. The empirical findings also confirmed the positive and significant impact of ICT Usage and readiness on economic growth for both ASEAN and EU. The results revealed that ICT usage's impact is more robust than ICT readiness. Further, the impact is more substantial in the EU than in the ASEAN region. The study identified precise ICT usage and readiness threshold levels. In this regard, the dynamic panel threshold regression findings are the prime contribution of the study. The dynamic panel threshold results in the ASEAN region have provided threshold levels of 71%, 524,228, and 27,713,029 for ICT usage (internet usage), ICT iv readiness (mobile phone subscription), and ICT readiness (fixed telephone connections), respectively. Similarly, dynamic threshold findings for the EU have confirmed threshold levels of 45%, 5,449,203, and 1,250,403 for ICT usage (internet usage), ICT readiness (mobile phone subscription), and ICT readiness (fixed telephone connections), respectively. The threshold results confirmed an overall saturation in ASEAN and EU regions considering ICT usage (Internet Users) and ICT readiness (Mobile Phone Subscription and Fixed Telephone Connections). It concluded that ICT usage and readiness impact in both regions is more significant and robust below the specified threshold levels than above the threshold.